Kebijakan Formulatif Sanksi Pidana Delik Korupsi Kerugian Keuangan Negara dalam KUHP Nasional Berbasis Tujuan Pemidanaan Deterrence - Alghifari, Habil; Elvany, Ayu Izza (Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This study discusses the urgency and application of the theory of the purpose of deterrence punishment in the formulative policy of criminal sanctions against corruption crimes of state financial losses which specifically refer to the criminal provisions in Statute Number 1 of 2023 concerning the Criminal Code (National Criminal Code) which is the lex posterior of Statute Number 31 of 1999 concerning the Eradication of Corruption. This study uses a normative legal research method, so this study uses a philosophical, conceptual and legislative approach method. The results of this study indicate that the construction of criminal sanctions for corruption crimes of state financial losses in the National Criminal Code does not reflect the purpose of deterrence punishment which can be seen from the lightness of the criminal sanctions applied in corruption crimes of state financial losses. The results of the next study are to form an ideal concept related to the formulated policy of criminal sanctions for corruption crimes of state financial losses in the National Criminal Code using the economic analysis of law approach.